Explosive-strength training improves 5-km running time by improving running economy and muscle power - Paavolainen, L.; Hakkinen, K.; Hamalainen, I.; Nummela, A.; Rusko, H. (Journal of Applied Physiology, 1999)
To investigate the effects of simultaneous explosive-strength and endurance training on physical performance characteristics, 10 experimental (E) and 8 control (C) endurance athletes trained for 9 wk. The total training volume was kept the same in both groups, but 32% of training in E and 3% in C was replaced by explosive-type strength training. A 5-km time trial (5K), running economy (RE), maximal 20-m speed (V20 m), and 5-jump (5J) tests were measured on a track. Maximal anaerobic (MART) and aerobic treadmill running tests were used to determine maximal velocity in the MART (VMART) and maximal oxygen uptake (VO2 max). The 5K time, RE, and VMART improved (P < 0.05) in E, but no changes were observed in C. V20 m and 5J increased in E (P < 0.01) and decreased in C (P < 0.05). VO2 max increased in C (P < 0.05), but no changes were observed in E. In the pooled data, the changes in the 5K velocity during 9 wk of training correlated (P < 0.05) with the changes in RE [O2 uptake (r = -0.54)] and VMART (r = 0.55). In conclusion, the present simultaneous explosive-strength and endurance training improved the 5K time in well-trained endurance athletes without changes in their VO2 max. This improvement was due to improved neuromuscular characteristics that were transferred into improved VMART and running economy.